Phenotypic and Functional Differences between Human Herpesvirus 6- and Human Cytomegalovirus-Specific T Cells - Fastenackels, Solène; Bayard, Charles; Larsen, Martin; Magnier, Philippe; Bonnafous, Pascale; Seddiki, Nabila; Appay, Victor; Gautheret-Dejean, Agnès; Sauce, Delphine (Journal of virology, 2019)
T cells are central to an effective defense against persistent viral infections that can be related to human cytomegalovirus (HCMV) or human herpesvirus 6 (HHV-6). However, knowledge of HHV-6-specific T-cell responses is limited. In order to deepen our knowledge of T-cell responses to HHV-6, we characterized HHV-6A- and HHV-6B-specific CD4 + and CD8 + T-cell responses directly ex vivo from healthy coinfected blood donors. Despite the strong similarity of HHV-6 and HCMV from a virologic point of view, we observed immunological differences, particularly in relation to the frequency and phenotype of effector/memory and regulatory virus-specific T cells. This suggests that different immune factors are solicited in the control of HHV-6 infection than in that of HCMV infection. Our findings may encourage immunomonitoring of patients with viral replication episodes to follow the emergence of effector versus regulatory T cells. Human herpesvirus 6 (HHV-6) infects >90% of the population and establishes a latent infection with asymptomatic episodes of reactivation. However, HHV-6 reactivation is associated with morbidity and sometimes mortality in immunocompromised patients. To date, control of the virus in healthy virus carriers and the failure to control it in patients with disease remain poorly understood. In particular, knowledge of HHV-6-specific T-cell responses is limited. Here, we characterized HHV-6A- and HHV-6B-specific CD4 + and CD8 + T-cell responses from peripheral blood mononuclear cells (PBMCs) of healthy donors. We studied the phenotype of effector HHV-6-specific T cells ex vivo , as well as of induced specific suppressive regulatory CD4 + T cells in vitro poststimulation, in comparison to human cytomegalovirus (HCMV) responses. Compared to that for HCMV, we show that ex vivo T-cell reactivity in peripheral blood is detectable but at very low frequency, both for HHV-6A and -6B viruses. Interestingly, the phenotype of the specific T cells also differs between the viruses. HHV-6A- and HHV-6B-specific CD4 + T lymphocytes are less differentiated than HCMV-specific T cells. Furthermore, we show a higher frequency of HHV-6-specific suppressive regulatory T cells (eTregs) than HCMV-specific eTregs in coinfected individuals. Despite the strong similarity of HHV-6 and HCMV from a virologic point of view, we observed immunological differences, particularly in relation to the frequency and phenotype of effector/memory and regulatory virus-specific T cells. This suggests that different immune factors are solicited in the control of HHV-6 infection than in that of HCMV infection. IMPORTANCE T cells are central to an effective defense against persistent viral infections that can be related to human cytomegalovirus (HCMV) or human herpesvirus 6 (HHV-6). However, knowledge of HHV-6-specific T-cell responses is limited. In order to deepen our knowledge of T-cell responses to HHV-6, we characterized HHV-6A- and HHV-6B-specific CD4 + and CD8 + T-cell responses directly ex vivo from healthy coinfected blood donors. Despite the strong similarity of HHV-6 and HCMV from a virologic point of view, we observed immunological differences, particularly in relation to the frequency and phenotype of effector/memory and regulatory virus-specific T cells. This suggests that different immune factors are solicited in the control of HHV-6 infection than in that of HCMV infection. Our findings may encourage immunomonitoring of patients with viral replication episodes to follow the emergence of effector versus regulatory T cells.